Cost-utility of pregabalin as add-on to usual care versus usual care alone in the management of peripheral neuropathic pain in Belgium. (May 2013) - Chevalier, Pierre; Lamotte, Mark; Van Campenhout, Hilde; Eyckerman, Roman; Annemans, Lieven
Abstract Background and objectives The cost effectiveness of pregabalin as an add-on to the standard treatment of Belgian patients with post-herpetic neuralgia (PHN) had been demonstrated in a previously published Markov model. The purpose of this study was to update that model with more recent cost data and clinical evidence, and reevaluate the cost effectiveness from the payer's perspective of add-on pregabalin in a wider set of NeP conditions. Methods: The model, featuring 4-week cycles and a 1-year time horizon, consisted in four possible health states: mild, moderate or severe pain and withdrawn from therapy. Three versions of the model were developed, using transition probabilities derived from pain scores reported in three placebo-controlled studies. The two treatment arms were 'usual care' or 'usual care + pregabalin'. Resource use and utility data were obtained from a chart review and unit costs from recent published data. The final outcome of the model was the incremental cost per quality-adjusted life-year (QALY) gained when adding pregabalin to standard care. Results: Based on 1000 simulations, two versions of the model showed that pregabalin was dominant respectively in 94.8% and 67.2% of the simulations, while the incremental cost per QALY was below €32, 000/QALY in respectively 99.1% and 94.6% of the simulations. The third version did not show cost effectiveness, despite an incremental cost of only €300 after 1 year. However, in the corresponding study, patients seemed less responsive to GABA analogs, since 55% of them had failed to respond to gabapentin before study inclusion. Limitations: The studies upon which the model is based have a short follow-up time as compared to the model horizon. The endpoints of two studies were only provided at the aggregated level and do not necessarily reflect the real practice. Conclusion: Based on this analysis, it can be concluded that from a Belgium payer perspective pregabalin offers a slight increase in quality of life in the studied populations as compared to standard care. Pregabalin is cost effective in the majority of cases except in one published clinical study, despite a low incremental cost per year (€300).